Analisis Kinerja Perusahaan Daerah Air Minum Tirta Benari Bajawa Dengan Pendekatan Balance scorecard - Gabriel Tanusi; Dafrosa Eno Keo (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2019)
This research aims to determine the performance of PDAM Tirta Benari Bajawa year 2015-2017 seen from the perspective of financial, customer, internal business, growth and learning. The data used in this research is quantitative data sourced from secondary data, financial report, and data published by PDAM Tirta Benari Bajawa from 2015 to 2017. Measurement of Financial Perspective performance using profit margins and return on invetment, measurement of customer perspective performance using customer acquisition aspects, customer retention, and pelagic profitability. Measurement of internal business process perspective performance using water-meter replacement aspect. Measurement of growth and learning perspective performance using employee training aspects. The results showed that the financial perspective is poor, because the company has not increased the sales volume of water well, causing the water sales turnover could not cover the cost-operational costs. The performance of the customer's perspective is poor, due to the average every year the number of new customers is not comparable to the number of subscribers as a result of the unoptimized service provided. Performance of internal business perspective is less good, this is due to management less attention to the change of meter whose economic age is over, causing a lot of water meter that is not functioning properly. The performance of the growth and learning erspective is lacking, this is because management pays attention to the development of employee-specific employee skills through technical training training. In general, the performance of the PDAM management Tirta Benari Bajawa is said to be less good, so that the management of the company should improve the service to customers through the distribution of water continuously every day so as to increase the volume Water sales and cover operational costs.